2014
DOI: 10.12693/aphyspola.125.18
|View full text |Cite
|
Sign up to set email alerts
|

Natural Bond Orbital (NBO) Population Analysis of 1-Azanapthalene-8-ol

Abstract: The molecular structure of 1-azanapthalene-8-ol was calculated by the B3LYP density functional model with 6-31G(d,p) basis set by Gaussian program. The results from natural bond orbital analysis have been analyzed in terms of the hybridization of atoms and the electronic structure of the title molecule. The stability of the molecule arising from hyper conjugative interactions, charge delocalization has been analyzed using natural bond orbital analysis. The electron density based local reactivity descriptors su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(39 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…Some conflicts are detected with the assignment of the C10 reported by R. P. Gangadharan et al (2014) in which the C10 containing LP(1) with high stabilization energy as 81.91 kJ/mol was reported.7 In the recent study, same reported method as B3LYP/6-31G(d,p) and new M06-2X/6-31G(d,P) method are used to clear this confusion from the literature. Anyway, there is no carbon of the molecule showed any lone pair [LP(1)] see Table 2 and 3.…”
Section: Fig 1: Structural Representation Of 8-hudroxyquinolinementioning
confidence: 99%
See 1 more Smart Citation
“…Some conflicts are detected with the assignment of the C10 reported by R. P. Gangadharan et al (2014) in which the C10 containing LP(1) with high stabilization energy as 81.91 kJ/mol was reported.7 In the recent study, same reported method as B3LYP/6-31G(d,p) and new M06-2X/6-31G(d,P) method are used to clear this confusion from the literature. Anyway, there is no carbon of the molecule showed any lone pair [LP(1)] see Table 2 and 3.…”
Section: Fig 1: Structural Representation Of 8-hudroxyquinolinementioning
confidence: 99%
“…8 Krishnakumar et al (2005) also reported FT-IR and FT-Raman spectra in gas phase. 9 R. P. Gangadharan et al (2014) reported NBO using B3LYP with 6-31G (d, p) basis set, 10 however, some discrepancies have been observed regarding the assignment of NBO analysis.…”
mentioning
confidence: 99%
“…Bond orbital analysis remains one of the most important parameters in the determination of electron density, charge transfer and atomic charge differences [35]. The orbital analysis was executed using the NBO program [36] implemented in the Gaussian 16 package.…”
Section: Natural Bond Orbitals (Nbos) Analysismentioning
confidence: 99%
“…The stabilization energy E 2 associated with i → j delocalization for a donor NBO ( i ) and an acceptor NBO ( j ) is calculated according to T1E2=qijF2i,jεjεi,where q ij represents the i th donor orbital occupancy and ε i and ε j are diagonal elements and F ( i , j ) off-diagonal elements, respectively, linked to NBO Fock matrix [31]. …”
Section: Computational Details and Theoretical Backgroundmentioning
confidence: 99%